Secure and Digitalized Future Mobility Shaping the Ground and Air Vehicles Cooperation - Cao, Yue (CRC Press, 2023)
This book discusses the recent advanced technologies in Intelligent Transportation Systems (ITS), with a view on how Unmanned Aerial Vehicles (UAVs) cooperate with future vehicles
Keywords: Electronic books